IMPACT OF MENTORING ON TEACHER’S TASK FULFILLMENT IMPROVEMENT AT SDN 3 BUNTOK AND SDN DANAU GANTING KABUPATEN BARITO SELATAN - Sri Murwantini; Mustabirin Alam (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The background of this research is that the weak understanding of teachers in Sekolah Dasar Negeri 3 Buntok and Sekolah Dasar Negeri Danau Ganting in Barito Selatan Regency on the process standard in Education National Standard that resulted in the learning process which is not in accordance with the mandate of Permendiknas No. 41 Tahun 2007. To overcome this, mentoring is done to teachers at both schools. For the conditions before and after the mentoring, the data are collected through document study and observation. The results of the analysis of the data obtained showed a significant impact on improving the quality of the implementation process of learning. Improved implementation of the learning process is supported by teacher’s better understanding of the standards process, RPP planning done not only for the paper work or copying someone else's, as well as the use of learning outcomes assessment to improve their RPP for the next meeting.